Automatic Temperature Management in Brooder and Its Effects on Chicken Growth and Body Weight - Irfan Ardiansah; Rudyanto Putra Simanjuntak; Wahyu K. Sugandi; Iwan Setiawan (Indragiri Islamic University, 2024)
The poultry industry, which plays a crucial role in meeting global meat and egg production demands, can benefit from research on optimal environmental conditions, particularly temperature and lighting, for chicken productivity, with a focus on local breeds like Sentul chickens and the use of brooders for temperature control. This research aims to create an integrated temperature control system for chicken brooder using an Arduino Uno microcontroller and web-based monitoring, which will automate the control of brooder and provide continuous monitoring to enhance efficiency and productivity in poultry farming, particularly for Sentul chickens, by accurately measuring and monitoring microclimatic conditions, preventing measurement errors and fluctuations in temperature, and mitigating potential stress-related issues. The developed control system simplifies monitoring and control processes, eliminating the need for direct human intervention, and consists of hardware components such as temperature sensors, incandescent lamps, a microcontroller, and a router, and software components including programming the sensors, microcontroller, and website for data display, and a temperature control program developed using the Arduino programming language that effectively regulates the heating lamp based on temperature thresholds. The study showcases the effectiveness and academic relevance of utilizing Arduino-based technology and web-based monitoring systems in poultry farming, providing valuable insights for chicken farmers and serving as a reference for future development of temperature control devices, ultimately enhancing the efficiency and productivity of Sentul chicken production and benefiting the local community and the poultry industry.